2017
DOI: 10.21009/ijer.04.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative and Self-Directed Learning Processes: A Case Study in Malaysian Chemistry PBL Lesson

Abstract: AbstrackProblem-based learning (PBL) (Lim, 2007;Abu Hassan Kassim, 2003;Anuar Zaini, et al., 2003;Ng & Siow, 2003; Sharifah Maimunah, 2000). Students learning are in the form of passively accepting information from the teacher, copying notes, drill and practice, Indonesian Journal of Educational Review, Vol. 4 (1), July 2017 2 and 'cookbook style' practical activities. In such a learning environment, students become passive and dependent learners. Students face difficulties in learning and working with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…They found that the implementation of PBL conducted consistently could enhance science learners' SDL. In a qualitative study with 35 chemistry learners in Malaysia, Peen and Arshad (2017) investigated collaboration and SDL in a PBL lesson. Their findings showed that both collaboration and SDL were enhanced in groups of learners during the implementation of PBL.…”
Section: Problem-based Learning and Self-directed Learningmentioning
confidence: 99%
“…They found that the implementation of PBL conducted consistently could enhance science learners' SDL. In a qualitative study with 35 chemistry learners in Malaysia, Peen and Arshad (2017) investigated collaboration and SDL in a PBL lesson. Their findings showed that both collaboration and SDL were enhanced in groups of learners during the implementation of PBL.…”
Section: Problem-based Learning and Self-directed Learningmentioning
confidence: 99%
“…Learning science effectively through the explicit instruction of scientific argument is often neglected (Foong & Daniel, 2013;Hasnunidah et al, 2015;Heng & Surif, 2013a, 2013bOsborne, 2015) including in practical work (Driver et al, 2000;Hasnunidah et al, 2015;Jiménez-Aleixandre et al, 2000;Kim & Song, 2006) when there is overemphasis in the curricula, textbooks, and among teachers on what students know at the expense of how students know (Osborne, 2010). Science learning is often executed in the form of students passively accepting information from the teacher, copying notes, doing drill and practice and "cookbook style" practical activities (Peen & Arshad, 2013). Such teaching and learning process does not promote students' potential (Akarsu et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The teaching and learning of science in Malaysia still focuses on teacher-oriented activities and does not expose students to argumentative tasks (Heng & Surif, 2013a;Heng, Surif, & Seng, 2014, 2015b. Moreover, the emphasis on high-stakes examinations (Abdullah & Francis Peters, 2015;Heng, Surif, & Seng, 2015a;Peen & Arshad, 2013;Peen & Arshad, 2014) reinforces the current practice of teaching of science in Malaysia. Hence, students need to be explicitly taught the elements of scientific argumentation and be involved in group-based argumentation sessions to justify their claim with evidence after the practical work sessions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the importance of the skills, but these were rarely adopted in science classrooms [7] [8][9] [10]. Science classrooms were dominated with 'chalk and talk' activities, notes-making, memorization, and simple question and answer activities [11] [12] [13]. Such activities provide students little chances to exercise their deep-thinking skills [14] that might bring low ability to think critically as well as to make scientific argumentations [10] that in turn will reduce their understanding about science concepts [15].…”
Section: Introductionmentioning
confidence: 99%